2013
DOI: 10.7774/cevr.2013.2.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for improved vaccines against foot-and-mouth disease epidemics

Abstract: Inactivated foot-and-mouth disease (FMD) vaccines are currently used worldwide. With the emergence of various FMD virus serotypes and subtypes, vaccines must become more suitable for field-based uses under the current circumstances in terms of the fast and proper selection of vaccine strains, an extended vaccine development period for new viruses, protecting against the risk of virus leakage during vaccine manufacture, counteracting the delayed onset of immune response, counteracting shorter durations of immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 57 publications
1
68
1
Order By: Relevance
“…Among these vaccine strains, A22 Iraq is reserved as a high-priority strain [18], while A Iran-05 is a recently added strain in the antigen bank [8]. The A Malaysia 97 strain protects against viruses prevailing in Southeast and East Asia [19] and is a widely used vaccine strain in many regions, including Korea [20].…”
Section: Discussionmentioning
confidence: 99%
“…Among these vaccine strains, A22 Iraq is reserved as a high-priority strain [18], while A Iran-05 is a recently added strain in the antigen bank [8]. The A Malaysia 97 strain protects against viruses prevailing in Southeast and East Asia [19] and is a widely used vaccine strain in many regions, including Korea [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that multivalent vaccines could provide clinical protection against FMD and mitigate large FMD outbreaks (Cox & Barnett, 2009;Elnekave et al, 2013;Park, 2013;Park et al, 2013). Despite the reported high efficacy of multivalent vaccines, the trivalent vaccine used in South Korea showed a low rate of antibody formation (60-80%) in the pig industry in South Korea from July 2011 to June 2012, according to type O ELISA assay (Park, 2013). Furthermore, there is considerable concern about the ability of trivalent vaccines to protect against the Andong strain, which is responsible for recent outbreaks in South Korea .…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence of various FMD virus serotypes and subtypes, vaccines must become more suitable for field-based uses under the current circumstances in terms of the fast and proper selection of vaccine strains and vaccine improvement should be based on using attenuated virus strains with high levels of safety through adoptation of the virus in the cell line [8].…”
Section: Introductionmentioning
confidence: 99%